Highly Sensitive, Naked Eye, and On-Spot Detection of pH Change Using Novel Phenothiazine Based Schiff Base - Anand, Vivek (Current Physical Chemistry, 2021)
Background: Visual pH sensors have received significant attention in the fields of environmental monitoring, analytical chemistry, food safety, and biomedicine. Therefore, a single organic moiety showing both naked-eye and fluorescence sensing of pH change is rare and in higher demand. Objective: A novel phenothiazine-based Schiff base PTz-SB was synthesized via facile organic transformations. This molecule showed promising naked-eye and on-spot pH sensing application, both using UV-visible and fluorescence techniques. Methods: The novel phenothiazine-based Schiff base was synthesized via facile organic transformation. The Schiff base was applied for both naked eye and fluorescence sensing of pH, using UV-visible and fluorescence techniques, respectively. Results: A Redshifts of 27 nm and 80 nm were observed in the λmax of absorption and emission spectra, respectively, on changing the pH from 12.2 to 1. The naked-eye pH sensing may be attributed to the change in colour from blue (higher pH) to dark green (lower pH), under daylight conditions. Furthermore, the change in fluorescence spectra is more pronounced. The fluorescence colour of the compound changes from dark blue to green and then finally to orange, on changing the pH from 12.2 to 4 to 1.5, respectively. Moreover, the electrochemical studies of the Schiff base were also procured. The bandgap obtained from the cyclic voltammetry studies was found to be 2.04 eV, which is characteristic of green emission. Conclusion: The easily synthesizable novel Schiff base can be utilized for real-life, on-spot practical application of pH sensing, which does not require sophisticated analytical instruments. Moreover, the time and cost of detection of pH using this thermally robust Schiff base are also very promising.
Keywords: pH sensor